Cocreating Public Value in Smart Cities: The Interplay of Citizen Engagement, Digital Literacy, and Governance Transparency - Dwibin Kannapadang; Siti Munawaroh; Sayugo Adi Purwanto (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
The expansion of smart city initiatives in rural and mountainous regions highlights the need to understand how public value is co-created within such contexts. This research aims to investigate the mechanisms of public value co-creation within the smart city ecosystem of Tana Toraja, a developing rural-mountainous region in Indonesia, by analyzing the interplay between digital literacy, governance transparency, and citizen engagement. This study employs a quantitative approach using SEM-PLS with data collected from 250 stratified respondents. The findings reveal that digital literacy serves as the most dominant antecedent, significantly dictating the depth of civic participation in digital platforms. While governance transparency directly enhances public value and accountability, its influence on active engagement remains moderate, suggesting that informational openness requires a baseline of public digital competence to be effective. The results confirm that public value is not merely a bureaucratic output but a co-created product resulting from the synergy between institutional transparency and empowered citizenship. This study recommends that local governments shift from being mere infrastructure providers to becoming digital education facilitators. Integrating community-based digital literacy programs with the deployment of telecommunication towers is essential to mitigate digital exclusion and ensure sustainable, inclusive smart city governance in rural contexts.